MOSES TO JOSHUA SUCCESSION MODEL IMPLEMENTING VISION INTEGRITY AND PASSION FOR CHRISTIAN LEADERSHIP - Yuco Aldelina; Stella Leoni (MAHABBAH: Journal of Religion and Education, 2026)
The primary objective of this research is to analyze the leadership succession model from Moses to Joshua, specifically examining the implementation of Vision, Integrity, and Passion (VIP) variables to address modern Christian leadership crises. Contemporary leadership in religious institutions often manifests a "value gap" the disconnect between confessed theological beliefs and functional values that govern actual practice. This phenomenon leads to systemic failures characterized by materialism, authoritarianism, and moral lapses, often summarized as the "Wealth, Throne, and Women" (HTW) paradigm. Utilizing a qualitative methodology through narrative exegesis of key biblical texts including Numbers 27, Deuteronomy 31, and Joshua 1 and a dialogue with the integrity of Christ in 1 Peter 2:21–23, the study identifies a normative framework for healthy regeneration. The findings reveal that successful succession is a meticulously planned process involving long-term mentoring, public commissioning, and the delegation of overlapping authority. The results demonstrate that the VIP model serves as a robust spiritual antithesis to leadership pathologies, restoring the gospel as the operational center of ministry. This study concludes that Christian institutions must adopt formalized mentoring and structural accountability to ensure the spiritual vitality of future leaders, particularly within the complex social dynamics and honor-shame cultures of Asia.